2020
DOI: 10.4049/jimmunol.204.supp.88.7
|View full text |Cite
|
Sign up to set email alerts
|

A novel, non-feeder-cell approach to generate large numbers of Cytokine-Induced Memory-Like NK cells for adoptive cells therapies

Abstract: We have constructed two heterodimeric multi-cytokine fusions, HCW9201 and HCW9206, to support a “Kick and Expand” approach to activate and induce proliferation of purified NK cells for adoptive cell therapy (ACT). HCW9201 is a heterodimeric fusion protein complex comprising human IL-15 (complexed with an IL-15Rα-sushi domain), IL-18 and IL-12. HCW9206 is heterodimeric fusion protein comprising human IL-15 (complexed with an IL-15Rα-sushi domain), IL-7, and IL-21. When purified human NK cells from peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The latest study found similar results, saying HCW9218 could be safely administered systemically to reduce senescent cells and alleviate senescenceassociated secretory phenotype in mice. It indicates that HCW9218 represents a novel immunotherapy and a clinically promising new class of senotherapeutic agents targeting cellular senescence-associated diseases (Shrestha et al, 2023).…”
Section: Il-15 Modification and Il-15/il-15rα Complexmentioning
confidence: 99%
“…The latest study found similar results, saying HCW9218 could be safely administered systemically to reduce senescent cells and alleviate senescenceassociated secretory phenotype in mice. It indicates that HCW9218 represents a novel immunotherapy and a clinically promising new class of senotherapeutic agents targeting cellular senescence-associated diseases (Shrestha et al, 2023).…”
Section: Il-15 Modification and Il-15/il-15rα Complexmentioning
confidence: 99%
“…Feeder cells also play an important role in the expansion of NK cells by providing cell-to-cell communication [ 61 ]. Although research continues to find new methods to reduce dependence on feeder cells and increase the efficiency of NK cell expansion, for example, the use of two heterodimeric multi-cytokine fusions for NK cell proliferation and activation [ 62 ].…”
Section: Strategies Of Nk Cell Immunotherapymentioning
confidence: 99%